One or Two Translators? Translation Technique and Theology of LXX Proverbs and Its Relation to LXX Job - Beeckman, Bryan (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2023)
In 1946, Gillis Gerleman proposed a single translator for LXX Proverbs and LXX Job. After he launched this hypothesis, scholars have either confirmed or debunked this hypothesis. Although attempts have been made to come up with an adequate answer to the question of a single translator for both Proverbs and Job, scholars have, thus far, not reached consensus. Moreover, the attempts that have been made are not at all elaborate. Thus, the question remains unsolved.This book tries to formulate an answer to the question of a single translator for both Proverbs and Job by examining the translation technique and theology of both books. The translation technique of both books is analysed by examining the Greek rendering of Hebrew hapax legomena, animal, floral, plant and herb names. The theology is examined by looking at the pluses in the LXX version which contain θεός and κύριος. The results of these studies are compared with one another in order to formulate an answer to a single translator. By doing so, this book not only formulates an answer to a single translator for both LXX Proverbs and Job but also characterises their translation technique and theology in greater detail